2021
DOI: 10.3233/ip-200301
|View full text |Cite
|
Sign up to set email alerts
|

The gendered digital turn: Canadian mayors on social media

Abstract: Women continue to occupy lesser positions of power at all political levels in Canada, although scholars still argue on the accessibility of municipal politics to women. However, no previous study has systematically examined the gender ratio of mayors across Canada, as well as their (active) use of social media platforms in a professional capacity. Using novel data, this study examines the variation in social media adoption and active use by gender outside of an electoral campaign. Results show that there is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The sample for this study was selected from a database (Sullivan 2021a) of 3,525 Canadian mayors that was created using Statistics Canada’s 2016 census, electoral results, as well as data from Facebook pages and Twitter and Instagram accounts. This original method of data collection began in mid-November 2018 and ended in mid-January 2019.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample for this study was selected from a database (Sullivan 2021a) of 3,525 Canadian mayors that was created using Statistics Canada’s 2016 census, electoral results, as well as data from Facebook pages and Twitter and Instagram accounts. This original method of data collection began in mid-November 2018 and ended in mid-January 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Canadian politics remains a male-dominated field, and although a (false) belief persists that municipal politics is closer to reaching gender parity, only a fifth of Canadian mayors are women (Sullivan 2021b). Despite the underrepresentation of women in mayoral positions across Canada, a higher proportion of women mayors have Facebook pages as well as Twitter and Instagram accounts and actively use them outside of electoral campaigns compared with men mayors (Sullivan 2021b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of the earliest research on social media use suggested that women generally use social media more actively (Hargittai, 2007) while at the same time considering that gender may influence how online campaigning is approached (Druckman;Kifer;Parkin, 2007), most studies focusing on politics on social media later showed that there are no differences between women and men in the use of social media ( 2011), some studies say that women are more active (Cook, 2017;Evans;Cordova;Sipole, 2014;Sullivan, 2021). Differences between studies about politicians may be related to the adoption of the technology at a given time within a given country and among citizens.…”
Section: Gendermentioning
confidence: 99%